Marriage concluded verbally, divorce without judicial intervention. A crossing of Esmara to Alicante - Lorente Martínez, Isabel (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
This study examines the consequences of a judicial decision to deny exequatur to a divorce processed without judicial intervention in Western Sahara. The couple married in accordance with the ritual of the tribes in that area, verbally. Subsequently, the marriage breaks up and they decide to divorce in Esmara. The wife applies to Novelda, Alicante, for the exequatur of that divorce. With these data, the challenge for the international privatist is served. The applicable legislation, the rigidity of the Spanish procedural rules and the axiological gap it raises will be analyzed.